Letter (copy) : Spanish Relief Statements - Tracey, Herbert
028-0103-001 HTT/HT/531 Publicity January 15, 1937 Mr. W. Adams, Victoria House Printing Co., 55-57, Drury Lane, London, W.C.2 Dear Bill, SPANISH RELIEF STATEMENTS. Herewith the addition to the Spanish Relief Statement. Proof when you come down on Monday morning please. Fraternally, Publicity Officer. 292/946/28/103